Experimental Study on Miniature Buckling-restrained Brace with Corrugated Core Bar. Issue 13 (3rd October 2022) - Gu, Tianyu; Li, Jiong-Hui; Sun, Jubo; Jia, Liang-Jiu; Liu, Tao; Ge, Hanbin
ABSTRACT: Miniature buckling-restrained braces (MBRBs) have been widely used as energy dissipating dampers in precast concrete and steel beam-to-column connections for their superior seismic performance. This paper proposes a new type of all-steel MBRBs with corrugated core bars, termed as corrugated MBRBs (CMBRBs), of which the core bars are confined by circular hollow section restraining tubes. Several D-shaped cuttings, termed as D-cuts, are made on core bar to improve ductility, so that the CMBRB can have a shorter length compared with conventional MBRBs, which leads to smaller installation space of the beam-to-column connections. Six specimens were designed and tested under cyclic loading to investigate effects of slenderness ratio and segment spacing-to-D-cut cross-section height ratio on seismic performance, and it was found that the two parameters have great effects on strength, stiffness, energy dissipation capacity and ductility. A theoretical model was established to predict stiffness and strength of the proposed CMBRB. Finally, a design procedure and recommended values for the parameters were proposed.